(untitled) (LACCEI, 2024)
Biopolymers has been considered suitable materials for the development of alternative packaging in particular, carrageenan and its composites has been explored for the development of flexible films and coatings because of its properties. The aim of this work was to develop carrageenan-based coatings for food packaging applications using anthocyanin from purple corn and oregano oil as additives. Samples of strawberries, swordfish, chicken breast and sausage were coated and evaluated for 30 days. In addition, biodegradability and characterization tests were performed by using spectroscopy and thermal analysis. Samples coated with coatings containing 5% w/w oregano oil demonstrated to inhibit the growth of mold fungus until for 15 days, while composites with 1% and 3% oregano oil presented mold after 5 days. Anthocyanin was added as a pH-indicator in films and films turn darker, indicating a degradation process form meats. Biodegradability tests showed that all formulations degrade following three stages, achieving a weight loss of 35% after 30 days. In conclusion, carrageenan-based coatings could be considered in packaging systems to increase the shelf-life of food. Oregano oil provides antifungal activity and anthocyanin give pH-responsiveness. The coatings demonstrated biodegradability and characterization demonstrated that the main structure of carrageenan in coatings was not altered.